SRATEGI PENINGKATAN PENJUALAN MAKANAN TRADISIONAL BATAK MELALUI DAYA TARIK PRODUK WISATA KULINER DI KOTA MEDAN - Zaina Balqis; Sagita Amelia Simorangkir; Wina Tri Lestari Hutabarat; Gebriella br. Tarigan (PT. Saha Kreasi Indonesia, 2025)
Medan boasts a significant culinary strength, particularly Batak cuisine, despite its relative lack of exposure to the general public and tourists. This research aims to develop a strategy for increasing sales of traditional Batak dishes by enhancing the appeal of culinary tourism in Medan. The research method used was a descriptive qualitative model, collecting data from various articles, journals, and relevant online sources related to promotion, cultural conservation, and culinary tourism. The results show that promotional methods through social media and food delivery apps are effective in attracting customers. Furthermore, preserving Batak cultural values through the presentation of dishes such as arsik, saksang, and naniura can reinforce the identity of regional cuisine. In conclusion, developing creative and culturally informed marketing methods can enhance the competitiveness of traditional Batak dishes as Medan's leading culinary icon.